2006
DOI: 10.1128/aem.00271-06
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Molecular Characterization of Tetracycline-Resistant Aeromonas veronii Isolates from Catfish

Abstract: Eighty-one tetracycline-resistant Aeromonas sp. strains were isolated from farm-raised catfish. Morphological and biochemical characteristics indicated that 23 of the 81 aeromonads were Aeromonas hydrophila, 7 isolates were Aeromonas trota, 6 isolates were Aeromonas caviae, 42 isolates were Aeromonas veronii, and 3 isolates were Aeromonas jandaei. However, the AluI and MboI restriction fragment length polymorphism (RFLP) patterns of the PCR-amplified 1.4-kb 16S rRNA gene from all 81 tetracycline-resistant aero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
93
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(103 citation statements)
references
References 28 publications
7
93
0
3
Order By: Relevance
“…The association of this gene with the chromosome was also observed (DePaola & Roberts 1995, Roberts 1996, which might explain its limited distribution among environmental samples, being more prevalent in polluted marine sediments (Andersen & Sandaa 1994, Chopra & Roberts 2001. Nawaz et al (2006), while describing the tetE gene, observed the high frequency of this determinant in Aeromonas spp. isolates.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The association of this gene with the chromosome was also observed (DePaola & Roberts 1995, Roberts 1996, which might explain its limited distribution among environmental samples, being more prevalent in polluted marine sediments (Andersen & Sandaa 1994, Chopra & Roberts 2001. Nawaz et al (2006), while describing the tetE gene, observed the high frequency of this determinant in Aeromonas spp. isolates.…”
Section: Discussionmentioning
confidence: 99%
“…There are some reports showing that the tetracyclineresistance determinants most predominant in Aeromonas species are tetA and tetE (Schmidt et al 2001b, Nawaz et al 2006). Our work is in agreement with the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Figueras et al, 2011b). Biochemical identifications in fact lack precision and tend to generate a lot of inconsistent results in comparison to those obtained by molecular methods (Beaz-Hidalgo et al, 2010;Figueras et al, 2011b;Kozińska et al, 2002, Kozińska, 2007Nawaz et al, 2006).…”
Section: Phenotypic Identification With Conventional Methods and Minimentioning
confidence: 99%
“…However, the importance of the species A. hydrophila is overestimated because biochemical identification systems erroneously identify up to 70-80% of the strains of Aeromonas as belonging to this species, when in fact they are many different species when identified by molecular methods (Beaz-Hidalgo et al, 2010;Figueras, 2005;2011b;Soler et al, 2003a). Prevalent motile species associated to diseased fish following molecular identification include A. veronii, associated with catfish, A. sobria with tilapia and trout, A. hydrophila with trout, A. bestiarum with carp and the recently described A. piscicola recovered from diseased salmonids and turbots (Beaz-Hidalgo et al, 2010;Kozińska, 2007;Li & Cai, 2011;Martino et al, 2011;Nawaz et al, 2006;Soriano-Vargas et al, 2010). Other motile species, such as A.…”
Section: Furunculosis and Other Aeromonas Fish Infectionsmentioning
confidence: 99%